Antioxidant Activities and Phenolic Content of Juniperus excelsa Extract: Antioxidant activities, Juniperus excelsa - Soheila Moein; Mahmoodreza Moein (Iranian Journal of Pharmaceutical Sciences, 2010)
Butyl-hydroxytoluene (BHT) is one of the major synthetic antioxidants with a wide range usage. Replacement of artificial antioxidants with natural antioxidants is highly considered. In this research, the antioxidant activity of Juniperus excelsa was investigated by using reducing power, DPPH radical scavenging and inhibition of lipid peroxidation. Also, the amounts of phenolic and flavonoid compounds were determined. Ethanol extract of Juniperus excelsa was fractionated based on increasing the polarity. The reducing power of ethyl acetate fraction was more than butanol fraction. The IC50 of ethyl acetate fraction (204.3±12.8 μg/ml) was less than that of butanolic (>400 μg/ml) fraction (p<0.0001). The IC50 of standard antioxidants such as BHT and gallic acid were 63.17±0.9 μg/ml and 2.49±0.06 μg/ml, respectively. In inhibition of b-carotene oxidation, ethyl acetate fraction had a remarkable effect (antioxidant activity coefficient, ACC= 960±20) which was more than the butanolic (ACC=550.7±15.3) fraction (p<0.01). The greastest amount of phenolic compounds (44.5±4.2 mg/g) and flavonoids (0.169±0.005 mg/g) were in ethyl acetate fraction. The results show that, the polar fractions of Juniperus excelsa, especially ethyl acetate, had more antioxidant activity.